2013
DOI: 10.3109/14767058.2013.804048
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between term pre-eclampsia and the risk of early childhood caries

Abstract: Pre-ecalampsia may not be associated with early childhood caries. A larger study and/or a study addressing the relation between pre-eclampsia and caries inducing lesions may provide more significant results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The majority of studies (28 out of 36) found no association between dental caries and premature birth, but four studies found that caries experience was more common among preterm children and another four studies found that caries experience was more common among full‐term children . Moreover, seven out of 50 studies found that caries experience was more common among children with LBW and only one study found that caries experience was more common among children with NBW . In other words, the findings of studies included in this review are not consistent, which led us to lower the certainty of evidence by one level.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The majority of studies (28 out of 36) found no association between dental caries and premature birth, but four studies found that caries experience was more common among preterm children and another four studies found that caries experience was more common among full‐term children . Moreover, seven out of 50 studies found that caries experience was more common among children with LBW and only one study found that caries experience was more common among children with NBW . In other words, the findings of studies included in this review are not consistent, which led us to lower the certainty of evidence by one level.…”
Section: Discussionmentioning
confidence: 87%
“…LBW may also be associated with enamel defects . Moreover, infants born with LBW may have a weak immune system, which could result in earlier colonisation by cariogenic micro‐organisms …”
Section: Introductionmentioning
confidence: 99%
“…Four studies presented results on caries prevalence by mode of delivery [19, 24, 26, 29]. The prevalence of caries varied across studies, ranging from 8.1 [19] to 67.0% [24].…”
Section: Resultsmentioning
confidence: 99%
“…A study that scored weak [24] reported significant differences in prevalence of dental caries by mode of delivery among children aged 3–5 years such that children born by cesarean section presented lower odds of dental caries than those vaginally delivered. Three studies that scored moderate [26, 29] to strong [19] reported no differences in dental caries prevalence between groups by mode of delivery (Table 4). …”
Section: Resultsmentioning
confidence: 99%
“…As with several other studies, we did not find being small for gestational age, spontaneous preterm birth or pre-eclampsia to be associated with dental caries in children. 19,21,22,37 However, Nirunsittirat et al found an inverse association between spontaneous preterm birth and childhood caries. 19 This study involved 544 four-year-old children from Thailand.…”
Section: Ta B L E 1 Hurdle Models Of the Relationship Between Pregnancy Complications And The Dmft Index In Six-year-old Childrenmentioning
confidence: 98%